2018
DOI: 10.1172/jci.insight.98942
|View full text |Cite
|
Sign up to set email alerts
|

Advances, challenges, and opportunities in extracellular RNA biology: insights from the NIH exRNA Strategic Workshop

Abstract: Extracellular RNA (exRNA) has emerged as an important transducer of intercellular communication. Advancing exRNA research promises to revolutionize biology and transform clinical practice. Recent efforts have led to cutting-edge research and expanded knowledge of this new paradigm in cell-to-cell crosstalk; however, gaps in our understanding of EV heterogeneity and exRNA diversity pose significant challenges for continued development of exRNA diagnostics and therapeutics. To unravel this complexity, the NIH co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 130 publications
0
34
0
Order By: Relevance
“…Beyond vesicles, this work mainly focused in extravesicular exRNAs, which have received very little attention 15 until recently 26 . In the past, we have compared the small RNA content between EVs and 100,000 x g supernatants of cell-conditioned medium and found that the non-EV fraction was highly enriched in 5’ tRNA halves of precisely 30 or 31 nucleotides and exclusively derived from glycine or glutamic acid tRNAs 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond vesicles, this work mainly focused in extravesicular exRNAs, which have received very little attention 15 until recently 26 . In the past, we have compared the small RNA content between EVs and 100,000 x g supernatants of cell-conditioned medium and found that the non-EV fraction was highly enriched in 5’ tRNA halves of precisely 30 or 31 nucleotides and exclusively derived from glycine or glutamic acid tRNAs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, exRNAs can achieve high extracellular stability by their association with proteins 13,14 . However, extracellular soluble ribonucleoproteins remain the least studied exRNA carriers 15 , with most attention thus far placed at the level of EVs. A new extracellular nanoparticle was recently discovered 16,17 , but the exact identity and RNA content of these complexes termed “exomers” needs further characterization.…”
Section: Introductionmentioning
confidence: 99%
“…ribosomal RNAs or mitochondrial DNA) [233,234] may be more likely to be present in certain EVs. However, several nuclear RNAs have been found in EVs, and a variety of data have been presented on specific versus non-specific incorporation of RNAs into EVs or subtypes of EVs [56,217,[235][236][237][238][239][240][241]. More research is thus needed before specific recommendations can be made for using nucleic acids as specific markers of EVs or EV subtypes.…”
Section: Characterization Of Evs By Their Protein Compositionmentioning
confidence: 99%
“…Even with more than a decade of intensive miRNA research, many issues in the field are still controversial, e.g., the competitive endogenous RNA hypothesis [230], non-seed sequence mediated binding of about a third of all Argonaute-associated mRNAs [47,86,[231][232][233], or the role of extracellular vesicle transfer of miRNAs [234] or whether 84% of all miRNAs truly exist, and how many are maintained during evolution [235,236]. These unsolved ambiguities of miRNA biology also impact prostate research since the perspective of the role of miRNAs seems to change with different authors' acknowledgment of disputed issues in miRNA biology [32].…”
Section: Discussionmentioning
confidence: 99%